Challenges of Human Resources (HR) Management in the Digital Era - Wildana, Saidati Nor; Nuril Shofiyah; Vicky Febriansyah; Iriani Ismail (Indonesian Journal of Economic & Management Sciences, 2023)
The aim of this research is to identify the challenges of managing human resources (HR) in the digital era at PT Sumber Alfaria Trijaya Tbk, Banyuajuh branch, Kamal Bangkalan. The method used is descriptive qualitative. Researchers used 2 data, namely secondary data and primary data. Secondary data was obtained from literature collections. Meanwhile, primary data was obtained through direct observation and interviews. The results of the research show that HR management in the digital era at PT Sumber Alfaria Trijaya Tbk Banyuajuh, Kamal, Bangkalan branch faces significant challenges